Pediatric out-of-hospital cardiac arrest: Time to goal target temperature and outcomes. (February 2019) - Moler, Frank W.; Silverstein, Faye S.; Nadkarni, Vinay M.; Meert, Kathleen L.; Shah, Samir H.; Slomine, Beth; Christensen, James; Holubkov, Richard; Page, Kent; Dean, J. Michael; ,
Abstract: Aim: Although recent out-of-hospital cardiac arrest (CA) trials found no benefits of hypothermia versus normothermia targeted temperature management, preclinical models suggest earlier timing of hypothermia improves neuroprotective efficacy. This study investigated whether shorter time to goal temperature was associated with better one-year outcomes in the Therapeutic Hypothermia After Pediatric Cardiac Arrest Out-of-Hospital Trial. Methods: Patients were classified by tertiles of time to attain assigned goal temperature range (32–34 °C or 36–37.5 °C) following ROSC. Outcomes in the first tertile ("earlier") Group 1 were compared with second and third tertiles ("later") Group 2. Separate analyses were, additionally, completed for hypothermia and normothermia intervention groups. Three one-year outcomes were examined: survival; Vineland Adaptive Behavior Scale (VABS-II) score ≥ 70; and decrease in VABS-II ≤ 15 points from baseline. Results: In the entire cohort (n = 281), median time from ROSC to goal temperature was 7.4 [IQR 6.2–9.7] hours: Group 1, 5.8 [IQR 5.2, 6.2] and Group 2, 8.8 [IQR 7.4, 10.4] h. Outcomes did not differ between these groups. For hypothermia subgroup, survival was lower in Group 1 than 2, [10/49(20%) versus 47/99(47%), p < 0.002], with a trend toward fewer with VABS-II scores ≥ 70 and change in VABS-II ≤ 15 points (p = 0.07–0.08). For normothermia subgroup, there was a trend toward higher survival in Group 1 than 2 [18/42(43%) versus 21/83(25%), p = 0.065], but no differences in VABS-II-related measures. In multivariable logistic regression models, no difference in earlier and later groups or temperature intervention was observed. Conclusion: We found no evidence that earlier time to goal temperature was associated with better outcomes.